Mindfulness and Meditation: The Most Potential Influences to Improve Adolescent Mental Health in East Java - Maghfiroh, Nasruliyah Hikmatul (West Science Interdisciplinary Studies, 2023)
This research explores the potential influences of mindfulness and meditation practices on adolescent mental health in East Java, Indonesia. Adolescence is a critical period marked by significant physical and emotional changes, making mental health a growing concern. Mindfulness and meditation have gained recognition globally as tools for enhancing mental well-being, but their effectiveness in East Java's cultural context remains underexplored. We employed a mixed-methods approach, combining quantitative 145 sample surveys and qualitative 5 informan interviews, to investigate this relationship comprehensively. The quantitative analysis revealed a statistically significant positive impact of mindfulness and meditation practices on mental health outcomes, with variations based on gender, age, and socio-economic status. Qualitative findings highlighted the cultural significance of these practices and the importance of community and family support. Despite the positive cultural attitudes, stigmatization of mental health issues remains a challenge. These results emphasize the need for culturally tailored interventions that integrate traditional values and address stigma, ultimately contributing to the well-being of East Javanese adolescents.